Educational antimicrobial stewardship programs in medical schools: a scoping review protocol. Issue 5 (May 2020) - Augie, Bashar M.; McInerney, Patricia A.; van Zyl, Robyn L.; Miot, Jacqui
ABSTRACT: Objective: The objective of this scoping review is to identify the available evidence on antimicrobial stewardship programs for teaching medical students about rational antimicrobial use, including the content taught and the method of instruction used. Introduction: Antibiotics are life-saving drugs and their discovery is one of the most important advances of the 20th century. They have transformed modern medicine by playing a critical role in the management of infectious diseases. However, the rapid development of resistance of pathogens to antibiotics is gradually affecting this initial success. Antimicrobial stewardship programs have been shown to reduce the burden of antimicrobial resistance in hospitals. Inclusion criteria: This scoping review will consider papers conducted in medical school curricula to improve the prescribing of antimicrobial medication. Studies that include other health profession students, such as nursing, pharmacy, or dentistry students, will be excluded. Studies published in English from 1996 onwards will be included. Methods: Databases to be searched are PubMed, Wiley Online library, CINAHL Complete, Web of Knowledge, Scopus and Education Resources Information Center. Unpublished studies and gray literature will be included. Searching will follow a three-step process and will be conducted by two reviewers. Data will be extracted by two independent reviewers. Any disagreements that arise between the reviewers during the study selection process or data extraction will be resolved through discussion, or with a third reviewer. Results will be presented in tabular or diagrammatic form, together with a narrative summary.